The host immune response to Clostridium difficile infection - Solomon, Katie (SAGE Publications, 2013)
Clostridium difficile infection (CDI) is the most common infectious cause of healthcare-acquired diarrhoea. Outcomes of C. difficile colonization are varied, from asymptomatic carriage to fulminant colitis and death, due in part to the interplay between the pathogenic virulence factors of the bacterium and the counteractive immune responses of the host. Secreted toxins A and B are the major virulence factors of C. difficile and induce a profound inflammatory response by intoxicating intestinal epithelial cells causing proinflammatory cytokine release. Host cell necrosis, vascular permeability and neutrophil infiltration lead to an elevated white cell count, profuse diarrhoea and in severe cases, dehydration, hypoalbuminaemia and toxic megacolon. Other bacterial virulence factors, including surface layer proteins and flagella proteins, are detected by host cell surface signal molecules that trigger downstream cell-mediated immune pathways. Human studies have identified a role for serum and faecal immunoglobulin levels in protection from disease, but the recent development of a mouse model of CDI has enabled studies into the precise molecular interactions that trigger the immune response during infection. Key effector molecules have been identified that can drive towards a protective anti-inflammatory response or a damaging proinflammatory response. The limitations of current antimicrobial therapies for CDI have led to the development of both active and passive immunotherapies, none of which have, as yet been formally approved for CDI. However, recent advances in our understanding of the molecular basis of host immune protection against CDI may provide an exciting opportunity for novel therapeutic developments in the future.